Modeling the change of beach profile under tsunami waves : a comparison of selected sediment transport models - Li, Linlin (2013)
In contrast to the efforts made to develop hydrodynamic models for large-scale tsunami propagation and run-up, little has been done to develop, test, and validate sediment transport models used to simulate tsunami-induced sediment movement. In this study, the performances of six widely-used sediment transport formulas are evaluated through case studies using an open source code XBeach, which is based on 2D depth-averaged nonlinear shallow water equations. Another open source code, Delft3D, is also used to see to what extent XBeach can give reliable results. The benchmarks used for case studies include three laboratory experiments and one field observation from a post-tsunami field survey conducted after the 2004 Indian tsunami. Our results show that most of the surveyed sediment transport formulas can give good results for laboratory-scale problems, but for real-scale problems, all six formulas failed to produce good results compared to those found in laboratory conditions. For laboratory-scale problems, both XBeach and Delft3D can predict satisfactory results with properly-chosen model parameters. For real tsunamis, high suspended sediment concentration may occur, and density stratification and hindered settling effect play an important role; therefore, Delft3D, with both hindered settling and density stratification being considered, may perform better than XBeach. The findings reported here will be useful for researchers and practitioners working on tsunami hazard mitigation.